Kritik Pemahaman Hadist Nabi Tentang Keutamaan Surat Al-Waqi'ah - Surahmat, Surahmat (INOVATIF: Jurnal Penelitian Pendidikan, Agama dan Kebudayaan, 2015)
Hadith Studies urgent put forward, especially the problem of understanding. In this study, the authors focused on the understanding of hadith criticism about the virtues of a letter al-Waqi'ah. Fairly comprehensive study has been written by Muhammad Makhdlori, Read Surah Al-Waqi'ah Then you will be rich. It is set out on the phenomena found in the community, some of which assume that the letter of al-Waqiah practice can cause a person to become rich. Is it true that this argument? The method I use is the hadith criticism in the sense mengkomparasikan hadith al-Waqi'ah letter with a variety of texts, both the Qur'an, hadith setema, and logic. After takhrij, this hadith al-Isnad da'if quality, nevertheless after study of matannya, then substance acceptable Hadith (maqbul) with understanding who read the letter al-Waqi'ah surely he would not hit indigent (poverty heart ) as Prophet Muhammad: wealth (intrinsic) is not in the abundance of things which have, however, lies in the wealth of a person's soul or heart (qona'ah; willingly accept any gift, sometimes a lot, sometimes a little, because only God alone more determine the extent of the needs of every servant).